Does Emotion Directly Tune the Scope of Attention?. (August 2013) - Huntsinger, Jeffrey R.
Considerable research supports a fixed link between affect and attentional scope, with positive affect producing a focus on the forest, so to speak, and negative affect producing a focus on the trees. New research, however, reveals greater flexibility in this link than is commonly assumed. Research consistent with the idea that affective feelings merely influence whether people act on briefly dominant tendencies to focus broadly or narrowly is presented. Implications of these new findings for research on affect and attention are discussed.